The Impact of Experimental Learning Techniques in Improving the Capability of Career Planning for Students - Zaroh, Septiani (Islamic Guidance and Counseling Journal, 2018)
The research is based on the low level of career planning ability of students in middle school. The main objective of the study is to know the impact of experimental learning techniques in improving the career planning ability of students. The research method used is quasi-experimental design. The subjects of the study were students of Class VIII SMP Negeri 1 Kalitidu. Bojonegoro academic year 2016/2017 which selected by purposive sampling technique. The technique of data analysis using the t-test to compare the gain value of experiment group and control group. The results showed t score is -8,303 and p score is 0,00 it means that experimental learning techniques can improve the career planning ability of the student than the conventional method.